Liver radioembolization with 90Y microspheres - Bilbao, José Ignacio. (Medical radiology. Diagnostic imaging, 2008)
This book provides an in-depth account of all aspects of radioembolization, a relatively novel technique based on the efficacy of radiotherapy for the treatment of liver tumors. In the past, the therapeutic radiation dose needed to treat a tumoral area has been sufficiently high to produce permanent damage to the nontumoral liver parenchyma. Radioembolization attempts to overcome this problem by combining embolization (intravascular deployment of particles) and brachytherapy (local administration of radiotherapy with the aid of a device, namely the particles themselves). The technique is based on improvements in percutaneous endovascular procedures which have allowed the deployment of small (25-35 µm) microspheres loaded with yttrium-90 that deliver high doses of beta-radiation specifically to the tumoral area. Performance of the procedure demands close familiarity with the hepatic vascular anatomy in order to ensure avoidance of vessels going to other territories. Furthermore, detailed knowledge of liver function, tumor volume, and liver vascular shunting is needed in order to calculate the appropriate therapeutic dose in each particular case. All of these topics are addressed in depth in this book, and initial clinical results are presented, showing that constant local control can be achieved with a reasonably low rate of complications. These promising results may lead to a progressive change in the therapeutic indication for radioembolization, and in some cases it could even become the therapy of choice. ⁹⁰Y Microspheres: concepts and principles -- Identification of candidates and selection criteria -- Radiological evaluation of patients with liver tumors -- Vascular anatomy and its implication in radioembolization -- Radioembolization : identifying and managing anatomic variants -- Posimetry and dose calculation -- Improving treatment design by image fusion techniques -- Nuclear medicine procedures for treatment evaluation -- Radiological detection and assessment of tumor response -- Results in hepatocellular carcinoma -- Results in liver metastatic colorectal cancer -- 90Y Microspheres for other liver metastases -- Use of ⁹⁰Y SIR-spheres in the treatment of unresectable hepatic metastases from neuroendocrine tumors -- Complications and side effects -- Future directions in radioembolization.